OC-075 Management and outcomes of oesophageal perforation: a national study of 2564 patients in england. (22nd June 2015) - Markar, SR; Mackenzie, H; Wiggins, T; Askari, A; Faiz, O; Zaninotto, G; Hanna, GB
Abstract : Introduction: Traditionally oesophageal perforation is a rare clinical emergency that confers a high rate of mortality and major morbidity. The aim of the present study was to determine patient and hospital-related factors associated with mortality from oesophageal perforation. Method: Patients admitted with a diagnosis of oesophageal perforation between 2001–2012 were identified. Comparative analysis was performed for the effect of hospital volume on clinical outcomes. Quartile thresholds used to divide hospitals were 1–14 (Lowest Volume (LV)), 15–20 (Low Middle Volume (LMV)), 21–35 (High Middle Volume (HMV)), and ≥36 cases (High Volume (HV)). Results: Over the twelve-year study period 2, 564 patients with oesophageal perforation were treated at 158 hospitals. The 30-day and 90-day mortality rates were 30.0% and 38.8% respectively. There was a significant increase in the percentage of patients managed supportively and a reduction in surgical management over time. Furthermore there were significant reductions in 30-day (36.6% to 24.9%; P < 0.001) and 90-day mortality (44.1% to 35.4%; P = 0.006) over the 12-year study period. Important patient demographics associated with 30-day and 90-day mortality included age ≥70, preoperative congestive cardiac failure, ischaemic heart, liver, and renal disease. High hospital volume was associated with significant reductions in 30-day (OR = 0.68; P = 0.001) and 90-day mortality (OR = 0.69; P = 0.001). Subset analysis of patients undergoing endoscopic intervention, identified hospital volume as an important factor associated with mortality. Conclusion: This study provides evidence for the centralization of management of oesophageal perforation to high volume centres with appropriate multi-disciplinary infrastructure to treat these complex patients. Disclosure of interest: None Declared.